2006
DOI: 10.1021/ic060964c
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Diffraction Studies of U4O9: Comparison with EXAFS Results

Abstract: Conradson et al. have analyzed X-ray absorption fine-structure spectra of the UO2-U4O9 system and concluded that oxygen atoms are incorporated in U4O9 as oxo groups with U-O distances in the range 1.72-1.76 A. They also found that the uranium sublattice consists of an ordered portion and an additional 'spectroscopically silent' glassy portion. We have carried out studies of powdered U4O9 by neutron diffraction which contradict these conclusions from EXAFS measurements. Our analysis shows that there are no U-O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 17 publications
(30 reference statements)
6
23
0
Order By: Relevance
“…The contribution of various U oxides phases depends on the conditions of the specific reactions (temperature/pressure and reacting agent) and knowledge of the U chemical state is prerequisite for a better understanding of the reaction paths as well as the crystallographic and thermodynamic properties.A large body of literature has been dedicated to studies of oxygen incorporation in UO 2+x. Neutron and X-ray powder diffraction experiments [17][18][19] showed that an increase of the oxygen content involves the distortion of the UO 2+x crystal structure. At least 14 distinct crystallographic structures were reported for U oxides during the transformation of UO 2 to U 3 O 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of various U oxides phases depends on the conditions of the specific reactions (temperature/pressure and reacting agent) and knowledge of the U chemical state is prerequisite for a better understanding of the reaction paths as well as the crystallographic and thermodynamic properties.A large body of literature has been dedicated to studies of oxygen incorporation in UO 2+x. Neutron and X-ray powder diffraction experiments [17][18][19] showed that an increase of the oxygen content involves the distortion of the UO 2+x crystal structure. At least 14 distinct crystallographic structures were reported for U oxides during the transformation of UO 2 to U 3 O 8 .…”
mentioning
confidence: 99%
“…One heavily debated topic was the observation of small U-O distances in the U 4 O 9 compound, which are characteristic for U(VI) compounds [20]. This was questioned by other theoretical and experimental works [18,21] that assumed that U 4 O 9 is a mixture of U(IV) and U(V).A number of studies to determine the U oxidation state for these systems have been reported using non-destructive spectroscopic methods: X-ray photoelectron spectroscopy (XPS) [13,22], electron energy-loss spectroscopy (EELS) [23], X-ray absorption near edge structure (XANES) [20,23,24] resonant inelastic soft X-ray scattering (RIXS) [25] and laserinduced fluorescence (LIF) spectroscopy [26]. Spectroscopic techniques often use the shifts in energy position of the main absorption/emission transitions in order to determine the U valence state.…”
mentioning
confidence: 99%
“…Comparison with calculations. The question of whether the broadening of the DOS to lower energies is expected or instead indicates an unusual phenomenon such as the condensate is addressed by DFT+U calculations 43 using the neutron-scattering type structure 10,13,54 that retains the fluorite lattice and incorporates the adventitious O into the vacant cubic sites concomitant with the displacement of some number of adjacent original O ions into neighboring sites. These calculations show (Fig.…”
Section: O Xas Of Standards and Uomentioning
confidence: 99%
“…At temperatures below those where rapid O diffusion eliminates crystallographic disorder there are two mixed valence compounds that are single phase in diffraction, U 4 O 9 and U 3 O 7 , although the multiplicity of their extended superlattices has prevented their structures from being completely solved. [10][11][12][13][14] Even in this ionic region, however, there are indications of more complexity, such as superionic conductivity of UO 2+x and the aggregation of the adventitious O in UO 2+x so that it is better described as UO 2 :U 4 O 9 and U 4 O 9 :U 3 O 7 mixtures. 10,15,16 At higher O:U ratios the structures are layered because of the propensity of U(V) and (VI) to form the trans dioxo species.…”
mentioning
confidence: 99%
“…However, this configuration of the defect cluster was just an assumption. Because, the lattice structure of the defect cluster observed in UO 2+x has been still discussed [19,20]. According to the phase diagram of U-O system [18], UO 2+x with 0 < x < 0.25 decomposes to UO 2+x and U 4 O 9Ày at low temperatures, and has a single phase of UO 2+x at temperature greater than $500 K. Therefore, for the present simulation condition such as x 6 0.09 and T P 900 K, UO 2+x has a single phase.…”
Section: Nemd Simulation Proceduresmentioning
confidence: 99%